A Combination of Importance-Performance Analysis and Gap Analysis for Improving Quality Service in a Pastry Company - Hirawati Oemar; Nugraha Nugraha; Maulida Dwi Amelia (President University, 2023)
PT. X is a well-known pastry company due to its consistent flavors and high product quality. PT. X saw a decrease in sales while competing businesses saw an increase. Based on the results of the preliminary questionnaire from 33 customers, it is known that customer satisfaction is a factor influencing the decline in sales experienced by PT X. The aim of this research is to identify the factors that influence customer satisfaction and the gap between consumers and management at PT. X and provide recommendations for improving PT. X's service quality to compete with similar companies. This study used an importance-performance analysis, a customer satisfaction index, and a gap analysis to enhance service quality. The findings showed that the customer satisfaction index had a value of 66.78% and that the Cartesian diagram of importance-performance analysis contained seven attributes in quadrant 1, indicating that these attributes require development. The gap analysis results indicate that all attributes have a negative gap value. To increase customer satisfaction, service quality must be improved based on the overall results of data processing. Making SOPs for employees, offering appealing promotions to customers, and rewarding and punishing employees for their efforts are among the recommendations made.